Improving CO2 assimilation efficiency in Cupriavidus necator H16 - Tibaldero, Giorgia (2021)
In this fast-developing world, there is an increasing demand for biodegradable and renewable materials derived from cheap and wildly available resources. Waste gases from industry (steel manufacturing, oil refining, coal and natural/shale gas) can be used as alternatives to petroleum-based solutions. In this context, the development of technologies allowing us to meet new trends and demands is becoming increasingly essential.